Pathology of systemic multiple bacterial infections and peritonitis in hatchery-produced African catfish Clarias gariepinus (Burchell, 1822) larvae - Thangapalam Jawahar Abraham; Harresh Adikesavalu; Sayani Banerjee (Journal of Fisheries, 2022)
Diseases are the major problems that have a significant impact on African catfish Clarias gariepinus seed production. This study reports the necropsy, microscopy, bacteriology and histopathology of diseased catfish larvae that experienced mass mortalities (>80%). The gill filaments of diseased larvae revealed no ectoparasites. The intestines had no parasitic association. About 35 – 40% of the dead larvae had ruptured abdomen. The affected larvae had abdominal haemorrhages and disintegrated intestine with marked degenerative and inflammatory changes, which indicated peritonitis. Bacteria including Aeromonas veronii, Edwardsiella tarda and Pseudomonas putida were isolated from the haemorrhagic exudates of diseased catfish larvae. Histopathology demonstrated dense melanomacrophage aggregates in the spleen. The intestine had extensive degeneration, basophilic margination and disintegration of the mucosal layer. The kidney section suggested a suppurative infection with necrosis of haematopoietic tissue, inflammation of the epithelial tissue, vacuolar degenerations and hypoplastic haematopoietic tissue. Aeromonas veronii and E. tarda immersion challenge at 5×106 cells mL–1 yielded no mortalities under laboratory conditions. Nevertheless, the hatchery management measures and the laboratory analyses supported peritonitis with systemic multiple bacterial infections in the observed large-scale motilities of excessively fed larvae.